(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Many a significant change in strategies of management accounting got In recent years, especially in the areas of reducing costs and performance Competitive, The entrance of the value chain has been used and the product life cycle, Because of what ails the traditional costs of inadequate systems as do not meet the requirements of the modern management, And to keep pace with progress in all fields, especially the industrial sector was the first researcher interest in this subject to the fact that the Kufa Cement plant is suffering from intense competition led to a decline in sales due to the dumping of the Iraqi market various types of cement and various origins policy Vouch cement product for 2015 phase gradient , Which reflected negatively on its ability to survive and grow in the market and keep it. The subject of the current research highlight the role of the value chain and product life cycle to assess the price competitiveness experienced by the cement producer, through a focus on his technique targeted cost as one of modern technologies in industrial product pricing as it depends on the market entrance in determining Competitive price that is through pleasing the customer and ensure their loyalty to the product. The hypothesis of research was formulated in order to identify and use Value Chain and life cycle cost tools in order to identify opportunities for cost reduction and assess the competitive advantage of the price.